Coexistence And Survival Strategy Model In BMT In Indonesia - Satria Yudha Bimantara; Muhammad Yazid (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
Through fatwa, the legal basis for the enactment of BMT in Indonesia, which acts as a fund collection and financing, all BMTs in Indonesia have a board responsible for supervising the consistency of the application of Sharia principles. Based on fatwa 130/DSN-MUI/X/2019 Guidelines for Deposit Insurance Institutions in the Implementation of Handling or Settlement of Islamic Banks Experiencing Solvency Problems, making the Sharia supervisory board continues to be an existence that needs to be considered more, related to Sharia principles in Sharia business contracts and treaties. Supported by Fatwa 90 / DSN-MUI / XII / 2013 Transfer of Murabahah Financing Between Islamic Financial Institutions (LKS), where people can obtain significant prosperity by knowing BMT. This institution is expected to continue to develop in the wider community to help or serve the community in the long term so that BMT can be ensured to live sustainably. The development of bmt in the future still needs reference as a reference for more advanced production in learning its evolution. This study uses a descriptive-qualitative research design with a juridical-normative approach to analyze the legal aspects related to BMT (Baitul Maal wat Tamwil). The data collection process involves gathering information from various reputable sources. The collected data is analyzed qualitatively with a juridical-normative approach, and the findings are verified through peer review and consultation with legal experts. The study provides insights into the legal principles and regulations governing BMT operations and proposes recommendations to close any gaps or inconsistencies in the legislation.